Public-private partnership systems in the Republic of Korea, the Philippines, and Indonesia - Kang-Soo Kim; Min-Woong Jung; Mee-Soo Park; Yoo-Eun Koh; Jin-Oh Kim (Asian Development Bank (ADB), 2018)
Infrastructure plays a critical role in boosting the economy's overall productivity and development toward improving the quality of life. Public-private partnership (PPP) is considered as one of the key modalities for sustainable infrastructure development. This paper analyzes and compares the PPP systems in the Republic of Korea, the Philippines, and Indonesia to identify the requirements for making this modality an effective catalyst for infrastructure's contribution to sustainable development. These countries have used the increased capacity and transactional experience in handling these partnerships to develop their PPP markets and strengthen their institutional framework to increase the use of PPPs to provide infrastructure services. A comparative analysis is then conducted to draw lessons for other economies in developing Asia seeking to improve the efficiency and effectiveness of their PPPs. The analysis underscores how strong institutions, unified procurement frameworks, and effective dispute resolution mechanisms can improve the implementation of infrastructure PPPs.
Keywords: H40; H50; O20; 330; infrastructures; legal and institutional frameworks; public-private partnership